Flipped classroom combined with human anatomy web-based learning system shows promising effects in anatomy education. Issue 46 (13th November 2020) - Yang, Chenchen; Yang, Xiaoxian; Yang, Hanqi; Fan, Yuqin
Abstract : Abstract: Flipped classroom has received much attention in medical education. The aim of this study was to evaluate the efficacy of flipped classroom combing with human anatomy web-based learning system in anatomy education. A total of 89 freshmen in medical specialty were enrolled and randomly allocated into either the experimental group (receiving the flipped classroom with human anatomy web-based learning system, n = 45) or control group (receiving the traditional classroom teaching, n = 44). A pre-quiz and a post-quiz were conducted before and after the classes, respectively. The improvement in scores between groups was compared. A 5-point Likert scale questionnaire was used to evaluate perceptions and experience. The mean pre-quiz scores of the 2 groups were comparable (all P > .05). However, the mean post-quiz score in the experimental group was significantly higher than that in the control group (91.44 ± 6.25 vs 86.13 ± 11.67, P < .05). The results of questionnaires showed that 44 (97.8%) students agreed with flipped classroom combined with human anatomy web-based learning system, 43 (95.6%) students obtained improved study interest in anatomy learning, and 42 (93.3%) students felt that the interactive, applied in-class activities during the class greatly enhanced their learning. Flipped classroom combined with human anatomy web-based learning system can be used as an effective learning tool for anatomy education.